(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The acting of the university in society can be seen through extension projects such as “Horta Escola” of the UCDB (Universidade Católica Dom Bosco). Created several years ago, it has contributed to the development of activities related to the cultivation of vegetables, medicinal plants and non-conventional food plants (PANC). The implementation of school vegetable gardens aims to influence students’ eating habits and serve as a living laboratory for the school subjects. Cultivations take place in the form of conventional vegetable gardens and also vertical vegetable gardens using the most different materials that schools, CRAs (Reference Center for Social Assistance), EMEIs (Municipal School of Early Childhood Education) and other entities provide. The partnership between the extension project and the communities served occurs through the implementation of vegetable gardens, technical monitoring, lectures and workshops. In the lectures and workshops, subjects such as choosing the area for the vegetable garden, irrigation, seedling production, phytosanitary control, humus production, cultural treatments, PANC, vertical gardens and healthy eating are addressed. During the phases that the vegetable garden passes until partner entity is able to conduct the garden independently, there is always a responsible person, who coordinates the activities, being that in schools and EMEIs he is usually one of the teachers and in CRAs he is the direction and the responsible for general care. It is noticed that this person is decisive for the success of the vegetable garden’s proposals. In schools and EMEIs the involvement of children is quite representative, especially in the early years. Children are very curious and report what they do in their homes about growing vegetables. In these institutions, teachers describe positive changes in students’ behavior, many wait anxiously for activities in the vegetable garden. Adolescents are more interested in the scientific aspects related to crops, with the majority participating in activities in the vegatable garden. The results obtained by the partnerships have shown that encouraging food production in the urban environment is extremely important and that many are interested and curious about the subject. It is also noticed that the implementation of vegetable gardens in a school environment serves as a showcase and can stimulate the use of urban areas for the production of a variety of foods, thus enriching the diet of the population involved and promoting changes in the eating habits of students and the entire school community.